Three-Dimensional Porous NiO Nanosheets Vertically Grown on Graphite Disks for Enhanced Performance Non-enzymatic Glucose Sensor. (20th August 2015) - Liu, Hu; Wu, Xiaolin; Yang, Bin; Li, Zhongjian; Lei, Lecheng; Zhang, Xingwang
Abstract: Vertically aligned 3D porous NiO nanosheets (s-NiO) were directly grown on graphite disks (GD) by chemical bath deposition via a surfactant template under mild reaction conditions. Such porous s-NiO as active electrode materials for non-enzymatic glucose sensors manifested a much better electrocatalytic performance than most of the existing electrodes of non-enzymatic glucose sensors, including a fast response time (<1 s), a high sensitivity (36.13 μA mM −1  mm −2 ), a wide linear range (up to 10.0 mM) and a low detection limit (0.9 μM at signal/noise ratio (S/N = 3) at a potential of 0.50 V ( vs . Ag/AgCl). Significantly, in comparison with the porous NiO nanofilms (f-NiO) fabricated by the traditional drop-coating method, the as-prepared porous s-NiO showed better stability towards the oxidation of glucose. The high electrocatalytic performance and stability were possibly attributed to the unique 3D porous structure of s-NiO. The 3D porous s-NiO vertically grown on GD (s-NiO/GD) could be a desirable electrocatalyst for enhanced performance non-enzymatic glucose sensor.